"Panie, do kogóż pójdziemy?" (J 6,68) / Antoni Jozafat Nowak. - Nowak, Antoni Jozafat (1935-2013)
1. "Jezus jest Panem" (Rz 10,9). 2. Chrystus kresem religii. 3. Chrystus - droga do Boga. 4. Chrystus - droga do człowieka.